Keterwakilan 30% Perempuan di Parlemen: Sebuah Refleksi Menyambut Pemilu 2024 - Rizky Octa Putri Charin (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2023)
Women's participation in politics is expected to be able to contribute significantly and be able to change views on